2023
DOI: 10.3389/fpubh.2023.1226438
|View full text |Cite
|
Sign up to set email alerts
|

Advances in myopia prevention strategies for school-aged children: a comprehensive review

Abstract: Myopia has significantly risen in East and Southeast Asia, and the pathological outcomes of this condition, such as myopic maculopathy and optic neuropathy linked to high myopia, have emerged as leading causes of irreversible vision loss. Addressing this issue requires strategies to reduce myopia prevalence and prevent progression to high myopia. Encouraging outdoor activities for schoolchildren and reducing near-work and screen time can effectively prevent myopia development, offering a safe intervention that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 114 publications
0
10
0
Order By: Relevance
“…Of these, 41 RCTs were included in the final analysis and summarized in tabular form (Supplementary Tables 2 – 7 ). Of the 140 review publications found, 18 reviews [ 9 , 12 , 19 , 45 , 54 – 67 ] published in the years 2019 to 2023, and retrieved via multiple searches, were considered, and included. In addition, some new myopia interventions, e.g., the cylindrical annular refractive element (CARE) lenses, were added later.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 41 RCTs were included in the final analysis and summarized in tabular form (Supplementary Tables 2 – 7 ). Of the 140 review publications found, 18 reviews [ 9 , 12 , 19 , 45 , 54 – 67 ] published in the years 2019 to 2023, and retrieved via multiple searches, were considered, and included. In addition, some new myopia interventions, e.g., the cylindrical annular refractive element (CARE) lenses, were added later.…”
Section: Resultsmentioning
confidence: 99%
“…Although spending time outdoors seems generally safe, it is nonetheless important to consider the potential risks linked to outdoor activities, which necessitates appropriate application of sun protection for both the eyes and skin [ 19 ]. Increased outdoor time is accessible to all individuals but may be constrained by social factors such as academic expectations, weather conditions, and seasonal variations [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations